Persistent inhibition of pore-based cell migration by sub-toxic doses of miuraenamide, an actin filament stabilizer. Issue 1 (December 2017) - Moser, Christina; Rüdiger, Daniel; Förster, Florian; Blume, Julia; Yu, Peng; Kuster, Bernhard; Kazmaier, Uli; Vollmar, Angelika; Zahler, Stefan
Abstract Opposed to tubulin-binding agents, actin-binding small molecules have not yet become part of clinical tumor treatment, most likely due to the fear of general cytotoxicity. Addressing this problem, we investigated the long-term efficacy of sub-toxic doses of miuraenamide, an actin filament stabilizing natural compound, on tumor cell (SKOV3) migration. No cytotoxic effects or persistent morphological changes occurred at a concentration of miuraenamide of 20 nM. After 72 h treatment with this concentration, nuclear stiffness was increased, causing reduced migration through pores in a Boyden chamber, while cell migration and chemotaxis per se were unaltered. A concomitant time-resolved proteomic approach showed down regulation of a protein cluster after 56 h treatment. This cluster correlated best with the Wnt signaling pathway. A further analysis of the actin associated MRTF/SRF signaling showed a surprising reduction of SRF-regulated proteins. In contrast to acute effects of actin-binding compounds on actin at high concentrations, long-term low-dose treatment elicits much more subtle but still functionally relevant changes beyond simple destruction of the cytoskeleton. These range from biophysical parameters to regulation of protein expression, and may help to better understand the complex biology of actin, as well as to initiate alternative regimes for the testing of actin-targeting drugs.